Surface water quality, public health, and ecological risks in Bangladesh—a systematic review and meta-analysis over the last two decades - Bilal, H.; Li, X.; Iqbal, Muhammad Shahid; Mu, Y.; Tulcan, R. X. S.; Ghufran, M. A. (Springer, 2023)
Water quality has recently emerged as one of the utmost severe ecological problems being faced by the developing countries all over the world, and Bangladesh is no exception. Both surface and groundwater sources contain different contaminants, which lead to numerous deaths due to water-borne diseases, particularly among children. This study presents one of the most comprehensive reviews on the current status of water quality in Bangladesh with a special emphasis on both conventional pollutants and emerging contaminants. Data show that urban rivers in Bangladesh are in a critical condition, especially Korotoa, Teesta, Rupsha, Pashur, and Padma. The Buriganga River and few locations in the Turag, Balu, Sitalakhya, and Karnaphuli rivers have dissolvable oxygen (DO) levels of almost zero. Many waterways contain traces of NO3, NO2, and PO4-3 pollutants. The majority of the rivers in Bangladesh also have Zn, Cu, Fe, Pb, Cd, Ni, Mn, As, and Cr concentrations that exceed the WHO permissible limits for safe drinking water, while their metal concentrations exceed the safety threshold for irrigation. Mercury poses the greatest hazard with 90.91% of the samples falling into the highest risk category. Mercury is followed by zinc 57.53% and copper 29.16% in terms of the dangers they pose to public health and the ecosystem. Results show that a considerable percentage of the population is at risk, being exposed to contaminated water. Despite hundreds of cryptosporidiosis cases reported, fecal contamination, i.e., Cryptosporidium, is totally ignored and need serious considerations to be regularly monitored in source water.